The European Union’s strategy on Afghanistan. Selected Issues - Sabawoon, Mirza (Wydawnictwo Nakowe WNPiD UAM w Poznaniu, 2019)
The attack on the World Trade Center of September 11, 2001 evidenced a growing terrorist threat to the US, as well as to the European Union. It is not surprising then that the EU started to combat terrorism abroad. Afghanistan posed such a large threat that the European community decided to actively participate in the war with the Taliban, and then in a peace mission in that area. The article analyzes the evolution of the European Union’s commitment to helping Afghanistan, democratization, reconstruction of the country and its structures, creation of civil society and improvement of the quality of life. The tenets of the latest EU strategy for Afghanistan in 2017 are also considered, which put the strongest emphasis on the issues of respect for human rights, increasing the role of women in social life and ensuring peace and stability in the region.

Zamach na World Trade Center z 11 września 2001 roku był dowodem na zwiększające się zagrożenie terrorystyczne dla USA, ale również dla Unii Europejskiej. Nie dziwi zatem, że UE zaczęła walczyć z terroryzmem również poza jej własnym obszarem. Afganistan stanowił na tyle duże zagrożenie, że wspólnota europejska zde cydowała się na czynny udział najpierw w wojnie z talibami, a następnie w misji pokojowej na tamtym terenie. Artykuł pozwala prześledzić ewolucję zaangażowania Unii Europejskiej w pomoc Afganistanowi, w sprawę demokratyzacji, odbudowy kraju i jego struktur, stworzenia społeczeństwa obywatelskiego oraz poprawę jakości życia. Pochylono się też nad zapisami najnowszej strategii UE dla Afganistanu z 2017 roku, która najsilniejszy nacisk kładzie na kwestie przestrzegania praw człowieka, zwiększenia roli kobiet w życiu społecznym oraz zapewnieniu pokoju i stabilności w regionie.
Strategia Unii Europejskiej wobec Afganistanu. Wybrane problemy
Keywords: Afghanistan; stability; strategy; European Union; democracy; human rights; security; Taliban European Union’s strategy on Afghanistan; Afganistan; stabilizacja; strategia; Unia Europejska; demokracja; prawa człowieka; bezpieczeństwo; talibowie